Robustness Estimation of Wireless MEMS Vibration Test under Harsh Environment - Changjian Deng (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Robustness estimation is important issue to ensure stability, reliability, and precision of Wireless MEMS vibration test under harsh environment stressing. Although the robustness of vibration test is limited mainly by the embedded electronics and sensors, how to obtain precise and robust data by using energy effective and resources constrained wireless sensor nodes is still a problem. Paper uses the multivariate uncertainty statistics method to estimate robustness of online test data under harsh environment, and uses Fisher information distance to estimate transmitting robustness in its complication communication process. Experiments and simulation are designed to analyze the robustness and precise of wireless MEMS nodes in numerical value, results show estimation methods and model are effective.